If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 4 = 2x + 6 Reorder the terms: 4 + y = 2x + 6 Reorder the terms: 4 + y = 6 + 2x Solving 4 + y = 6 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + y = 6 + -4 + 2x Combine like terms: 4 + -4 = 0 0 + y = 6 + -4 + 2x y = 6 + -4 + 2x Combine like terms: 6 + -4 = 2 y = 2 + 2x Simplifying y = 2 + 2x
| 0.50x+0.15(50)=34.5 | | 2(0)+3y=36 | | 1.4x^2+.9x-31.7=0 | | (x-3)+3x+(x-1)=61 | | xy^3-16xyz^3= | | 2x-10=6-9x | | 2(-x+3)-5=9 | | 39/949 | | 3(8x-1)+7(x+5)=-59 | | 9=-6w+3(w-6) | | 4=12-d | | 15k=k-2 | | -7.6=0.4-4y | | 5x*5=180 | | 2.3x=12 | | 22=4(y+8)-6y | | -7/8x=49 | | -15r=r-7 | | -2+15+x=-4+8 | | 11x+66=21 | | 12=9-c | | 5x+2x+6x= | | 4(n+2)+3(2n+6)= | | 75+64+x=180 | | 7=3m+1 | | 2y+3y=30x | | a(2ab-5c)= | | 2x+y-3x=1 | | 2x-3(-2x+22)=-130 | | 3j+4=10 | | 201=17b+99 | | 6=2-b |